Soil fertility management in sub-Saharan Africa - Masso, C.; Nziguheba, Generose; Mutegi, J.; Galy-Lacaux, C.; Wendt, J.; Butterbach-Bahl, Klaus; Wairegi, L.W.I.; Datta, A. (Springer, 2017)
Most of the population in sub-Saharan Africa depends on agriculture for livelihood, which is mainly practiced by resource-constrained smallholder farmers. Due to persistent low crop yields, food and nutrition insecurity, farmers have been opening new lands through deforestation or encroachment into marginal lands where possible, seeking for additional yields, which has aggravated soil erosion, land degradation, and eutrophication of water bodies. Adoption of integrated soil fertility management practices in the smallholder farming systems has been affected by several factors including poor access to improved agricultural inputs, poor understanding of the practices and their benefits, and importantly limited financial capacity.